Introducing the "The Importance of Context, Scale, and Interdependencies in Understanding and Applying Ostrom's Design Principles for Successful Governance of the Commons" - Edella Schlager (International Journal of the Commons, 2016)
Editorial for: The role of context, scale, and interdependencies in successful commons governance